Connectivity Revolution: Fiber Optic Network Mapping for Modern Jember - Darmawan, Muhammad Riza; Fadhil, Martiana Kholila; Rizkiyah R., Candra Putri; Pratama, Dananjaya Endi; Triputradi, Moh. Erdianto (Jurnal Arus Elektro Indonesia, 2024)
Jember Regency is a popular marine tourism destination with five beaches, each experiencing an increase in the number of visitors each year in Jember Regency. Although these beaches are favorites and increase visitors annually, they require better infrastructure to support tourism activities. The research evaluated the network design using several parameters: power link budget, rise time, Signal to Noise Ratio (SNR), and Bit Error Rate (BER). The result of this study shows that the 39 network paths meet the BER calculation standard of 10-12 and the SNR standard of 21.5 dB.